Wojna polsko-polska a kryzys postindustrialny - Mazurczak, Jacek (Refleksje. Pismo naukowe studentów i doktorantów WNPiD UAM, 2018)
The author presents the Polish – Polish war issue by using the post-industrial crisis theory. He concentrates on the A. Toffler’s theory of the Second and Third Wave and on the term of Superfight. According to the author, the two sides of Polish – Polish war are the supporters of both the Second Wave and the Liquid Modernity. Polish – Polish war will be increasing while supporters of the Liquid Modernity accept the ideas accurate for the Third Wave.